Machining of metal directed energy deposited components - Oyelola, Olusola (2020)
The current manufacturing focus on the reduction of design to part time coupled with the need for more sustainable and economically viable delivery of intricate parts has led to a corresponding interest in the development of metal additive manufacturing processes. This interest has led to parts from these processes being deployed commercially for various applications from aerospace to biomedical functions. However, current limitations of metal additive manufacturing methods requires the post processing of components produced in this way for eventual use in demanding engineering applications. The tolerances, surface/bulk integrity and homogeneity in builds consistent with typical production specifications cannot, in most cases, be achieved within a single process. Hence, researchers have begun to address this need through research targeted at improving upon these shortcomings. This study investigates the post-processing of components produced using directed energy deposition. Components produced using these techniques often require post-processing to achieve dimensional tolerances and match end user surface requirements. Heat treatments, grinding, machining amongst other steps are often used in the achievement of surface improvement. Since additively manufactured components differ from wrought materials in terms of microstructure and by extension, mechanical properties, it follows the machinability of these components also differ to those of wrought materials. This has been proven to be the case. This present work focuses on the influence of build parameters on the resulting machinability of the components, the use of heat treatments for improving machinability and most importantly, the development of machining strategies for post processing components produced from these technologies. Heat treatments are found to cause a differentiation in measured cutting forces causing a percentage drop when comparing between the as built directed energy deposition component and a beta heat treated component by up to 40 % and 16 % at the same cutting speed for an alpha heat treated component . In the development of machining strategies, an adaptive machining system for the machining of these components has been developed on an open architecture machine tool. This accommodates for the machining of anisotropic (changing) microstructures which are commonplace in metal AM components. The development of this system is also influenced by the need for seamless machining of functionally graded components which are produced using AM systems. The use of adaptive machining of deposited components is shown in this study to lead to an improvement in surface finish in milling and drilling operations. Improvement in surface roughness in milling experiments show a reduction of up to 70% in surface roughness and 55% in subsurface deformation depth when comparing machined surfaces. Drilling trials show lower variation in values – up to 2 % in surface finish. However, an important finding - the effects of variation in cutting forces as machining progressed through the varying microstructure is reported here – variations of up to 15 % (up to 100N) are recorded with increased number of holes drilled and tool use increased – this is correlated to the microstructural variation and grain refinement due to the reheating process during addition of subsequent layers. Thus, towards obtaining these results, the study encompasses the deposition of materials, characterising before post-processing, post-process machining the components and characterisation after post-processing. Also, the influence of machining strategies on residual stress, surface and subsurface finish condition are all investigated.